Molecular Mechanism of Action of 2‐Ferrocenyl‐1, 1‐diphenylbut‐1‐ene on HL‐60 Leukemia Cells. Issue 11 (25th August 2014) - de Oliveira, Alane Cabral; da Silva, Emanuella Gomes; Rocha, Danilo Damasceno; Hillard, Elizabeth A.; Pigeon, Pascal; Jaouen, Gérard; Rodrigues, Felipe A. R.; de Abreu, Fabiane C.; da Rocha Ferreira, Fabrícia; Goulart, Marilia O. F.; Costa‐Lotufo, Letícia V.
Abstract The aim of this work was to investigate the mechanism of action of 2‐ferrocenyl‐1, 1‐diphenylbut‐1‐ene (1) on HL‐60 human leukemia cells. While inactive against noncancerous cells, 1 provoked a concentration‐dependent decrease in viable tumor cells, primarily via apoptosis, as evidenced by analysis of cell morphology, activation of caspases 3 and 7, increased DNA fragmentation, and externalization of phosphatidylserine. Necrosis was observed only at the highest tested concentration (4 μM). Compound 1 interfered with the cell cycle, causing an accumulation of cells in the G1/G0 phase. Interaction of 1 with dsDNA and ssDNA was observed by differential pulse voltammetry and confirmed by hyperchromicity in the UV/Vis spectra of dsDNA, with an interaction constant of 2×104 M−1. Both the organic analogue 1, 1, 2‐triphenylbut‐1‐ene (2) and ferrocene were inactive against cancer and noncancer cell lines and did not react with DNA. These results reinforce the idea that the hybrid strategy of conjugating ferrocene to the structure of tamoxifen derivatives is advantageous in finding new substances with antineoplastic activity.